Diplomacy and audit: Technologies of knowledge in Europe. (January 2016) - Kuus, Merje
Highlights: Provides a quasi-ethnographic account of diplomatic work in Europe. Analyzes the impact of audit culture on knowledge production. Synthesizes the work on governmentalized subject-production in geography, anthropology, and related fields. Advances practice-based approaches to the study of policy. Advances critical study of foreign policy practice. Abstract: This article investigates diplomatic knowledge production in Europe—mostly in European Union institutions but also in the member states—to probe the role of audit culture in that professional field. Diplomatic knowledge refers to the knowledge about places that is produced by career diplomats; audit culture refers to a form of regulatory power that shapes thought and action through the continuous application of measurable standards. Empirically, the analysis draws from nearly one hundred interviews with policy professionals, mostly but not exclusively in Brussels, to examine the play of qualitative and intangible skills in diplomatic work. Conceptually, it foregrounds the growing impact of audit in that sphere. I observe the narratives of efficiency, economy, and flexibility in European diplomacy, and I highlight tensions around the value of different forms of knowledge in the profession. By foregrounding the intellectual and creative facets of diplomatic work and by examining the impact of audit culture on the profession, the article helps us understand how diplomats produce knowledge about the world. It thereby enriches geographical scholarship on geopolitical knowledge and policy processes.